The Effect of Management Audits, Recruitment, and Training on Employee Performance at The Ismail Medika Clinic in Depok - Ismail Kusumah; Eddy Hermawan Hasudungan; Irawan R.D Budianto (International Journal Labs, 2026)
Employee performance is a critical factor in maintaining service quality, operational efficiency, and patient satisfaction in healthcare institutions. At Ismail Medika Clinic in Depok, employee performance is influenced by the effectiveness of human resource governance, particularly management audits, recruitment, and training. This study aims to analyze the partial and simultaneous effects of management audits, recruitment, and training on employee performance. The research employed a quantitative cross-sectional approach with a census sampling technique involving all 45 employees, consisting of both medical and non-medical personnel. Data were collected using a structured questionnaire and analyzed through multiple linear regression using SPSS version 27. The findings show that management audits have a positive and significant effect on employee performance, with a t-value of 4.344 and a significance value below 0.001. Recruitment also has a positive and significant effect, with a t-value of 3.074 and a significance value of 0.004. Training, however, has a positive but statistically insignificant effect, with a t-value of 0.314 and a significance value of 0.755. Simultaneously, the three variables significantly affect employee performance, with an F-value of 10.737 and an R² of 0.440. The study concludes that effective audits and competency-based recruitment are essential drivers of employee performance, while training programs require more careful planning and systematic evaluation.